Coercive Law. (12th January 2022) - Adams, Thomas
Abstract: In this review article I consider Kenneth Einar Himma's argument that law is necessarily coercive. While casting doubt on Himma's framing of the issues as well as on his specific claims in support of that conclusion, I suggest some alternate avenues for arguing that law is a coercive institution.